Nurse practitioners' time on nonbillable activities. Issue 9 (September 2018) - Kippenbrock, Thomas; Lo, Wen-Juo; Emory, Jan; Buron, Bill; Odell, Ellen; Reimers, Jennifer
ABSTRACT: Background and purpose: During the provision of patient care delivery, all providers, including nurse practitioners (NPs), spend some time in activities that are not reimbursable. Understanding these nonbillable activities is crucial to the economic viability and success of existing and projected practice models. This study explored and compared seven nonbillable activities occurring in the practices of NPs in various settings. Methods: Using a nonexperimental, descriptive design, 509 NPs were surveyed about nonbillable activities encountered in daily practice. Binomial regression analyses and incidence rate ratios were used to interpret relationships between each variable and nonbillable time. Conclusions: Although not every variable had significance, there were significant differences found in the amount of time spent in certain nonbillable activities depending on workplace setting, number of support staff, and primary care provider role. Implications for practice: The uncertainty of health care reform, including reimbursement, provider shortage, and the expanding roles of NPs, requires a closer look at both billable and nonbillable care activities. Understanding how nonbillable time affects work efficiency, costs, and the value of NPs will allow NPs to influence future health care reimbursement policies and delivery care models.